Thermoresponsive copolymer-grafted SBA-15 porous silica particles for temperature-triggered topical delivery systems - S. A. Jadhav; D. Scalarone; V. Brunella; E. Ugazio; S. Sapino; G. Berlier (eXPRESS Polymer Letters, 2017)
A series of poly(N-isopropylacrylamide-co-acrylamide) thermoresponsive random copolymers with different molecular weights and composition were synthesized and characterized by attenuated total reflectance Fourier-transform infrared (ATR-FTIR), differential scanning calorimetry (DSC), size exclusion chromatography (SEC) and proton nuclear magnetic resonance (NMR) spectroscopy. The lower critical solution temperatures (LCST) of the copolymers were tuned by changing the mole ratios of monomers. Copolymer with highest molecular weight and LCST (41.2 °C) was grafted on SBA-15 type mesoporous silica particles by a two-step polymer grafting procedure. Bare SBA-15 and the thermoresponsive copolymergrafted (hybrid) SBA-15 particles were fully characterized by scanning electron microscope (SEM), ATR-FTIR, thermogravimetric analysis (TGA) and Brunauer-Emmett-Teller (BET) analyses. The hybrid particles were tested for their efficiency as temperature-sensitive systems for dermal delivery of the antioxidant rutin (quercetin-3-O-rutinoside). Improved control over rutin release by hybrid particles was obtained which makes them attractive hybrid materials for drug delivery.